2022
DOI: 10.1186/s12902-022-01113-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of T-cell immunoreceptor with immunoglobulin and tyrosine-based inhibitory motif domains (TIGIT) in anaplastic thyroid carcinoma

Abstract: Background Immune checkpoint proteins have not been fully examined in follicular cell-derived thyroid carcinoma and medullary thyroid carcinoma (MTC). Anaplastic thyroid carcinoma (ATC) is one of the most aggressive carcinomas. Even multimodal treatment does not result in favorable clinical outcomes for patients with ATC. Anti-tumor immunity has therefore been highlighted as having therapeutic promise for ATC. Methods We examined a novel immune che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…These findings justify and explain the success of TIGIT immunotherapy in PD-L1+ non-small cell lung carcinoma [11,38]. TIGIT expression was also documented on tumor cells, especially in cutaneous melanoma [39], choroidal melanoma [40], thyroid cancer [41], undifferentiated pleomorphic sarcoma [42], lung adenocarcinoma [43], and esophageal cancer [44]. An interesting study has also demonstrated TIGIT expression on CD20+ TILs in gastric cancer [45], where cases with higher TIGIT+CD20+ infiltrates exhibited a worse prognosis.…”
Section: Tigit As An Immunohistochemical Biomarker: Current Knowledgementioning
confidence: 62%
“…These findings justify and explain the success of TIGIT immunotherapy in PD-L1+ non-small cell lung carcinoma [11,38]. TIGIT expression was also documented on tumor cells, especially in cutaneous melanoma [39], choroidal melanoma [40], thyroid cancer [41], undifferentiated pleomorphic sarcoma [42], lung adenocarcinoma [43], and esophageal cancer [44]. An interesting study has also demonstrated TIGIT expression on CD20+ TILs in gastric cancer [45], where cases with higher TIGIT+CD20+ infiltrates exhibited a worse prognosis.…”
Section: Tigit As An Immunohistochemical Biomarker: Current Knowledgementioning
confidence: 62%
“…Endogenous peroxidase was removed using 3% hydrogen peroxide, and the sections were then blocked with goat serum before being incubated with primary antibodies, including anti-CTHRC1 (1:500, ab256458; Abcam, UK), anti-E-Cadherin (1:100, ab235682; Abcam, Cambridge, UK), anti-Vimentin (1:200, #5741; Cell Signaling Technology, Danvers, MA, USA), anti-Snail (1:50, A5243; ABclonal Science Inc., Woburn, MA, USA) overnight at 4 °C. The sections were then incubated with a secondary antibody for 1 h at 25 °C, followed by color development using diaminobenzidine (DAB), counterstaining with hematoxylin, differentiation with hydrochloric acid ethanol, dehydration using an ethanol gradient, the sections were cleared in xylene and imaged ( Nakazawa et al, 2022 ). All immunohistochemical stainings were evaluated blindly and independently by two investigators.…”
Section: Methodsmentioning
confidence: 99%